Implikasi Procedural Time-Limits atas Gugatan Keputusan Administrasi Negara (Studi Banding: Indonesia, Australia, Kanada) - Moch Chafid; Anna Erliyana (Administrative Law and Governance Journal, 2020)
Abstract The purpose of this study is to analyze the impact of the procedural time limit on state administrative decisions set out in the Administrative Law in Indonesia, Australia and Canada. The research method used by the writer is descriptive-comparative analysis. That is to conduct a comparative analysis of the impact of the procedural time limit on state administrative decisions in Indonesia, Australia and Canada based on the specified procedural time limit parameters. The results showed that the limit of ninety days after the announcement or receipt of a state administrative decision in Article 55 of Law Number 5 Year 1986 concerning State Administrative Courts has implications for the loss of the right of judicial review, the bias in the substance of the lawsuit, flexibility in judicial procedures, and weakened supervision of administrative decisions of state officials in Indonesia. In contrast to the procedural time limit provisions in commonwealth countries such as Australia and Canada, where the constitution features an extension of the procedural time limit and the discretion given to federal court judges to reject or accept claims, extending the lawsuit deadline, even though the deadline has expired. Keywords: Implication; Procedural Time Limit; State Administrative Decree Abstrak Tujuan penelitian ini adalah melakukan analisis dampak terhadap ketentuan batas jangka waktu pengajuan gugatan (procedural time limit) atas keputusan administrasi negara yang diatur dalam Undang-Undang Administrasi di Indonesia, Australia dan Kanada. Metode penelitian yang digunakan penulis adalah deskriptif-comparative analisis, yaitu melakukan analisa perbandingan dampak batasan jangka waktu prosedur gugatan keputusan administrasi negara di Indonesia, Australia dan Kanada berdasar parameter procedural time limit yang ditentukan. Hasil penelitian menunjukkan bahwa batasan sembilan puluh hari semenjak diumumkan atau diterimanya keputusan administrasi negara di Pasal 55 Undang-Undang Nomor 5 Tahun 1986 tentang Peradilan Tata Usaha Negara, berimplikasi hilangnya hak judicial review, biasnya substansi gugatan, fleksibilitas prosedur acara peradilan, serta melemahnya pengawasan terhadap keputusan administrasi pejabat negara di Indonesia. Berbeda dengan ketentuan procedural time limit di negara-negara commonwealth seperti Australia dan Kanada, konstitusinya memberikan fitur perluasan makna procedural time limit dan diskresi yang diberikan kepada hakim pengadilan federal untuk menolak atau menerima gugatan, memperpanjang batas waktu gugatan, meski batas waktunya sudah berakhir. Kata kunci: Implikasi; Batasan Waktu Prosedural; Keputusan Administrasi Negara